2012
DOI: 10.1111/wre.12000
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing potential germination period of weeds with base temperatures and base water potentials

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
88
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 32 publications
15
88
1
3
Order By: Relevance
“…The values of t b estimated for batches 1 of a. retroflexus (10.0 ± 1.30°C to 12.3 ± 0.40°C) were slightly lower than those for batches 2 (12.0 ± 1.27°C to 12.9 ± 0.37°C), but no significant differences could be detected. Moreover, all these values were in complete agreement with previous findings obtained on two Italian populations of a. retroflexus (Masin et al 2010) while a significantly lower t b value of about 9°C was reported by Guillemin et al (2013) for a French population. Regarding a. hybridus, no proper value of t b has ever been reported but a previous study observed little germination at 10°C and none at 5°C (Steckel et al 2004), supporting the range of t b estimated in the present experiment (7.6 ± 1.73°C to 9.6 ± 0.25°C).…”
Section: Discussionsupporting
confidence: 92%
“…The values of t b estimated for batches 1 of a. retroflexus (10.0 ± 1.30°C to 12.3 ± 0.40°C) were slightly lower than those for batches 2 (12.0 ± 1.27°C to 12.9 ± 0.37°C), but no significant differences could be detected. Moreover, all these values were in complete agreement with previous findings obtained on two Italian populations of a. retroflexus (Masin et al 2010) while a significantly lower t b value of about 9°C was reported by Guillemin et al (2013) for a French population. Regarding a. hybridus, no proper value of t b has ever been reported but a previous study observed little germination at 10°C and none at 5°C (Steckel et al 2004), supporting the range of t b estimated in the present experiment (7.6 ± 1.73°C to 9.6 ± 0.25°C).…”
Section: Discussionsupporting
confidence: 92%
“…Estudo realizado por Guillemin et al (2013) A elevada amplitude dos valores de germinação entre temperaturas encontrada neste estudo pode estar associada ao grau de dormência presente nas sementes, sobretudo nas primeiras épocas de avaliação após a colheita delas. A dormência em sementes é uma característica comum de muitas espécies de plantas daninhas e de grande importância ecológica, destacando-se que a quebra da dormência nas sementes pode ser proporcionada por diversos fatores, principalmente luz, temperatura de incubação, estratificação por frio e nitrogênio (Tang et al, 2008).…”
Section: Resultsunclassified
“…O potencial de germinação da semente e emergência de uma plântula é determinado pela combinação de vários elementos, como temperatura do solo, potencial hídrico, luz, condições gasosas e teor de nitrato (Guillemin et al, 2013). A temperatura é provavelmente o principal fator ambiental que controla a germinação, tanto em culturas quanto em plantas daninhas, atuando diretamente na porcentagem e na taxa de germinação -isso quando outros fatores essenciais para esse processo não estão limitantes no meio (Martinkova et al, 2006).…”
Section: Introductionunclassified
“…Early emergence of common ragweed likely reflects its specific soil temperature and moisture germination requirements (Guillemin et al 2013). Shepherd's-purse [Capsella bursa-pastoris (L.) Medik.…”
Section: Timings That Resulted In Similar Weedmentioning
confidence: 99%